MYCOPLASMOSIS, CHLAMYDIOSIS AND BRONCHIAL ASTHMA FROM ETHNOGENETIC POSITION - A. O. Sharavii (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Article contains the data on frequency of mycoplasmosis and chlamydiosis of different pathogenic forms of bronchial asthma (BA) in the city of Krasnoyarsk and town of Kyzil in regard to ethnical belonging. The problems of Mycoplasma and Chlamydia pathogenicity as a whole had been discussed. We have determined clinical peculiarities of mycoplasmosis and chlamydiosis in BA: low-grade fever, obtrusive cough with purulent sputum dyspnea and respiration function (RF) disturbances of mixed character.